First Report of Root Rot on kiwifruits Caused by Athelia rolfsii in Hefei, China - Liu, Qianwen; Wang, Hanyang; Song, Wenpeng; Yu, Jiuming; Huang, Lu; Cheng, Hao; Lan, Jianbin; Zhang, Lixin; Liu, Yongsheng; Tang, Wei (Plant disease, 2021)
Kiwifruits (Actinidia ssp.), known as "King of vitamin C", have been wildly cultivated. In August 2020, about 15% of A. deliciosa (cv. Xuxiang) and A. macrosperma (rootstock) plants displayed symptoms typical of root rot at a farm in Hefei (117°25'E, 31°86'N), Anhui Province of China (Fig.1 a-b). Symptoms first appeared at the root and stem junction which were covered by cottony white mycelium during warm and humid summer. Then, the infected tissues were rotted, and subsequently the whole plant withered. Tan to brown sclerotia were observed on the basal stem epidermis and soil surface surrounding the stem (Fig.1 c-d). Infected plant tissues and sclerotia were collected for isolating the fungal pathogen. The samples were surface sterilized in 70% alcohol for 30 s, followed by 2% sodium hypochlorite for 3 min, washed five times with sterile double-distilled water (ddH2O), dried, placed on potato dextrose agar, and incubated at 25 °C in the dark. In total, twelve fungal isolates were obtained. The mycelia of all the isolates were white with a fluffy appearance (Fig.1 e). Sclerotia formed after 7 days were initially white (Fig.1 f) and gradually turned to dark brown (Fig.1 g) measuring 0.67 to 2.03 mm in diameter (mean = 1.367 ± 0.16 mm; n = 30). Hyphae were hyaline, septate. Some cells possessed multiple nuclei (Fig.1 h) and clamp connections (Fig.1 i). No spores were observed. For species-level identification, ITS1/ITS4 and EF1-983F/EF1-2218R primers were used to amplify the internal transcribed spacer regions (ITS) and translation elongation factor-1 alpha regions (TEF-1α), respectively (White et al. 1990; Rehner & Buckley 2005). Based on ITS and TEF-1α sequence analyses, all 12 isolates were categorized into two groups, group one including isolates NC-1 and NC-6~10 and group two containing NC-2~5 and NC-11~12. The length of ITS sequences for NC-1 (MW311079) was 684bp and 99% to 100% similar to Athelia rolfsii (MN610007.1, MN258360.1). Similarly, ITS sequences for NC-2 (MW311080) were 99% to 100% similar to A. rolfsii (MH858139.1; MN872304.1). Also, TEF-1α sequences of NC-1 (MW322687) and NC-2 (MW322688) were 96% to 99% similar to sequences of A. rolfsii (MN702794.1, GU187681.1, MN702789.1). Based on morphology and phylogenetic analyses (Fig.1 j&k), the isolates NC-1 and NC-2 were identified as Athelia rolfsii (anamorph Sclerotium rolfsii) (Mordue. 1974; Punja. 1985). To fulfill Koch's postulates, ten sclerotia of NC-1 were incorporated into the soil near stems of healthy Xuxiang plants (Fig.2 a). Similar treatments were also used for plants of A. macrosperma or A. arguta (Fig.2 g&m). Each control group had the same number of plants (n=3) for inoculating with ddH2O. The plants were kept in an incubator with a relative humidity of 80% and temperature of 28°C with 16/8 hours light/dark photoperiod. After twenty days, the pathogen-inoculated plants developed similar symptoms of root rot observed in the field (Fig.2 b-d, h-j, n-o). Similarly, four days after inoculation with sclerotia, leaves developed water-soaked lesions (Fig.2 e, k&p). No significant difference in pathogenicity was observed between NC-1 and NC-2. Non-inoculated control plants remained disease-free (Fig.2 f, l&q). The pathogenicity experiments were repeated three times. The pathogen was re-isolated from infected tissues and sclerotia, and isolates were confirmed as A. rolfsii by the ITS sequences. A. rolfsii has been reported to cause root rot in kiwifruit in the USA (Raabe. 1988). To our knowledge, this is the first report A. rolfsii causing root rot on kiwifruits in China.